Contemporary Croatian Philosophy - Kukoč, Mislav (Array, 2007)
The article starts with the short survey of the history of Croatian philosophy from the Middle Ages up to the post-World War Two period. Development of the Croatian praxis philosophy is presented in the central part of the paper. In their concluding remarks the authors described recent growing pluralisation of the philosophical life in Croatia.